Encyclopedia of the U.S. government and the environment : history, policy, and politics - Lindstrom, Matthew J., 1969- (ABC-CLIO, 2011)
With the election of Barack Obama, the environmental policy of the United States is expected to shift away from the approach of George W. Bush. It won't be the first time in U.S. history that a new president has made a break with the previous administration's environmental approach.
Keywords: Environmental policy -- United States -- Encyclopedias.; Environmental policy -- United States -- History -- Encyclopedias.; Environnement -- Politique gouvernementale -- États-Unis -- Encyclopédies.; Environnement -- Politique gouvernementale -- États-Unis -- Histoire -- Encyclopédies.; SCIENCE -- Environmental Science.; Environmental policy; United States; Encyclopedias; History